Skewed X chromosome inactivation in girls and female adolescents with autoimmune thyroid disease - Suttikarn Santiwatana (2019)
© 2018 John Wiley & Sons Ltd Objective: Skewed X chromosome inactivation (XCI) was associated with female predominance in adult autoimmune thyroid disease (ATD). In normal females, skewed XCI is increased with age. Whether early-onset skewed XCI is associated with childhood ATD remains unknown. This study aimed to determine XCI skewing in paediatric ATD. Design, Patients and Measurements: Ninety-one female ATD patients, aged 3-20 years and 57 age-matched, female controls were enrolled. XCI was analysed by enzymatic digestion of DNA with methylation-sensitive enzymes followed by PCR of the polymorphic CAG repeat in the androgen receptor gene. Skewed XCI was defined as having 80% or greater of the cells preferentially inactivated on the same X chromosome. XCI pattern of the enrolled patients and parental origin of the skewed XCI were determined. Results: After exclusion of samples with homozygous CAG repeats, skewed XCI was analysed in 83 patients (57 Graves' disease and 26 Hashimoto thyroiditis) and 52 controls. There was an increased frequency of skewed XCI in ATD patients as compared with the controls (23% vs 8%, P = 0.022). Patients with Hashimoto thyroiditis had greater frequency of skewed XCI than patients with Graves' disease (38% vs 16%, P = 0.023). There were no differences in clinical parameters between patients with skewed and random XCI. Analysis of 7 patients with skewed XCI showed a preferential inactivation of paternal X chromosome in 6 patients (86%). Conclusions: Frequency of skewed XCI was increased in childhood ATD. This observation suggests a possible association of skewed XCI in the development of paediatric ATD.